Differential regulation of FGFR3 by PTPN1 and PTPN2. Issue 2 (17th December 2014) - St‐Germain, Jonathan R.; Taylor, Paul; Zhang, Wen; Li, Zhihua; Ketela, Troy; Moffat, Jason; Neel, Benjamin G.; Trudel, Suzanne; Moran, Michael F.; Pandey, Akhilesh; Moran, Michael F.
<x xml:space="preserve">Abstract</x> Aberrant expression and activation of FGFR3 is associated with disease states including bone dysplasia and malignancies of bladder, cervix, and bone marrow. MS analysis of protein‐phosphotyrosine in multiple myeloma cells revealed a prevalent phosphorylated motif, D/EYYR/K, derived from the kinase domain activation loops of tyrosine kinases including FGFR3 corresponding to a recognition sequence of protein‐tyrosine phosphatase PTPN1. Knockdown of PTPN1 or the related enzyme PTPN2 by RNAi resulted in ligand‐independent activation of FGFR3. Modulation of FGFR3 activation loop phosphorylation by both PTPN1 and PTPN2 was a function of receptor trafficking and phosphotyrosine phosphatase (PTP) compartmentalization. The FGFR3 activation loop motif DYYKK650 is altered to DYYKE650 in the oncogenic variant FGFR3K650E, and consequently it is constitutively fully activated and unaffected by activation loop phosphorylation. FGFR3K650E was nevertheless remarkably sensitive to negative regulation by PTPN1 and PTPN2. This suggests that in addition to modulating FGFR3 phosphorylation, PTPN1 and PTPN2 constrain the kinase domain by fostering an inactive‐state. Loss of this constraint in response to ligand or impaired PTPN1/N2 may initiate FGFR3 activation. These results suggest a model wherein PTP expression levels may define conditions that select for ectopic FGFR3 expression and activation during tumorigenesis.